Inhibition of quorum sensing-controlled biofilm formation in Pseudomonas aeruginosa by quorum-sensing inhibitors. (October 2017) - Kalaiarasan, Ellappan; Thirumalaswamy, Kottha; Harish, Belgode Narasimha; Gnanasambandam, Vasuki; Sali, Veeresh Kumar; John, James
Abstract: Antimicrobial therapy against extensively drug-resistant (XDR) P. aeruginosa biofilms is less efficient compared to the treatment of equal bacterial counts of free-floating planktonic cells, which has become a serious threat in hospital environment. P. aeruginosa regulate their cooperative activities and physiological processes through a cell to cell chemical communication process called Quorum sensing (QS). This attracted our interest to synthesize, and to chemically characterize two anti-QS compounds, N -(4-4-fluoroanilno butanoyl) -l -homoserine lactone (FABHL) and N -(4-4-chlororoanilno butanoyl) -l -homoserine lactone (CABHL) to inhibit biofilm formation via disabling the QS circuits. Structural and morphological properties of these compounds were characterized by 1 H Nuclear Magnetic Resonance (NMR), 13 C NMR and High-resolution mass spectrometry (HRMS). Two biofilm forming XDR P. aeruginosa isolates were included in this study. Anti-biofilm property of FABHL or CABHL was confirmed by biofilm formation assay and it was shown to occur without affecting the bacterial growth. Anti-QS property of FABHL or CABHL was determined by evaluating the expression levels of QS genes ( lasR and rhlR ) by quantitative real time PCR (qRT-PCR). Although, FABHL and CABHL downregulates the expression levels of QS genes, lasR expression was significantly reduced. Molecular modeling studies revealed that the binding energy of FABHL and CABHL with LasR protein was −4.27 and −4.51, respectively. Hence, the synthesized compounds have the potential to serve as a potent anti-biofilm agent via disabling the QS systems. Lethality of FABHL and CABHL against PBMCs was assessed by 3-(4, 5- dimethylthiazol-2-yl)-2, 5-diphynyl tetrazolium bromide (MTT) assay. Cell viability was observed for both the compounds. Highlights: Two anti-QS compounds, l FABHL andl CABHL were synthesized and characterized successfully. FABHL and CABHL have the potential to serve as a potent anti-biofilm agent of P. aeruginosa . FABHL and CABHL downregulate the expression levels of QS genes in P. aeruginosa . Enhanced binding efficiency of FABHL or CABHL with LasR protein of P. aeruginosa .